2019
DOI: 10.1111/dme.14093
|View full text |Cite
|
Sign up to set email alerts
|

The association between diabetes medication and weight change in a non‐surgical weight management intervention: an intervention cohort study

Abstract: Aim To compare weight change in a lifestyle-based weight management programme between participants taking weight-gaining, weight-neutral/loss and mixed diabetes medications.Methods Electronic health records for individuals (≥ 18 years) with Type 2 diabetes who had been referred to a nonsurgical weight management programme between February 2008 and May 2014 were studied. Diabetes medications were classified into three categories based on their effect on body weight. In this intervention cohort study, weight cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This study adds more support for prescribing weight-neutral/losing diabetes medications to patients with class 3 obesity in medical programs for weight loss. Aldekhail et al showed that patients with T2DM prescribed a weight-neutral/losing medication lost more weight than those prescribed weight-gaining medication [ 30 ]. Our study supports this finding although we showed that changing to weight-neutral/losing medications during the program was associated with more weight loss than changing to weight-gaining medications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study adds more support for prescribing weight-neutral/losing diabetes medications to patients with class 3 obesity in medical programs for weight loss. Aldekhail et al showed that patients with T2DM prescribed a weight-neutral/losing medication lost more weight than those prescribed weight-gaining medication [ 30 ]. Our study supports this finding although we showed that changing to weight-neutral/losing medications during the program was associated with more weight loss than changing to weight-gaining medications.…”
Section: Discussionmentioning
confidence: 99%
“…Electronic and paper records were reviewed to obtain demographic details and medical history including anthropometry, medications, and blood results. Diabetes medication prescribing was classed as weightneutral/losing and weight-gaining as previously described in Aldekhail et al [30]. The weight-neutral/losing class was composed of patients on metformin only or metformin combined with a SGLT-2 inhibitor, a DPP-4 inhibitor, or a GLP-1 agonist.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations